Interlude. Paths of Destiny. Rosalía's Spiritual Car Ride in AUNQUE ES DE NOCHE Interlude. Paths of Destiny - Eva Meienberg (Journal for Religion, Film and Media, 2020)
A critical review of Rosalia's music video for "Aunque es de noche" that focusses on media-transmitted, personal spirituality, female strength and the amalgamation of religious imageries.